Information Communication Technology and Human Resource Management in Modern Organisations: A Concept for 21st Century - Chepkuto, Paul; Kipsang, Stanley; Kungu, Mwangi (International Journal of Social Sciences and Management, 2015)
Human resource information system is a database system that has been developed to provide the necessary assistance to HR in terms of decision making and reporting of information. It is basically one of the key elements that is critical in the overall management information system (MIS) of an organization. It is an IT-enabled HR service available to the HR managers for data analysis and decision making. HRIS provides the necessary support to the HR managers in making a quality decision by ensuring that there is adequate and timely relevant information that is available. The scope is so wide that it can provide information about every aspect of an employee, starting with his recruitment and ending with his retirement. As such, HRIS facilitates the use of computer technology to streamline HR operations, cut costs and eventually enhance the effectiveness of human resource management. As technology evolves, so does its impact on strategic human resource planning. Human resource information systems are electronic systems that compile information in databases to be easily accessed and analyzed. Some information systems allow automation of processes, such as payroll tax calculations, while others streamline processes by minimizing the need for manual data entry and paper records, thus increasing accuracy and efficiency DOI: http://dx.doi.org/10.3126/ijssm.v2i2.122898 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 102-107